2020
DOI: 10.3390/vaccines8040728
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of COVID-19 Pandemic in Patients with Moderate to Severe Plaque Psoriasis Receiving Systemic Treatments

Abstract: Chronic plaque psoriasis is an inflammatory skin disease affecting 2–3% of the general population. Approximately one-third of patients are candidates for systemic immunosuppressive treatments, such as synthetic or biological disease-modifying antirheumatic drugs, because of disease extensions, localization in sensitive or visible areas and/or resistance to topical treatments. These therapies have been associated with increased risk of infection, including upper respiratory tract viral infection. Psoriasis is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 47 publications
(58 reference statements)
0
29
0
Order By: Relevance
“…[4][5][6][7][8] Nevertheless, patients with psoriatic disease appear to have similar rates of infection with SARS-CoV-2 and COVID-19 outcomes as the general population, with multiple new studies from Italy, which primarily focused on patients with psoriasis receiving oral or biologic treatment, supporting our initial recommendation (guidance 1.1). [9][10][11] Additional new studies of patients with psoriatic arthritis (PsA) nested within cohorts of patients with rheumatic disease also suggest that they have similar rates of infection with SARS-CoV-2 and COVID-19 outcomes as the general population. [12][13][14] However, the risk of COVID-19 in autoimmune diseases was higher than in control patients (odds ratio [OR], 2.19; 95% confidence interval [CI], 1.05-4.58) in a meta-analysis of 7 case-control studies.…”
Section: Capsule Summary Dmentioning
confidence: 99%
“…[4][5][6][7][8] Nevertheless, patients with psoriatic disease appear to have similar rates of infection with SARS-CoV-2 and COVID-19 outcomes as the general population, with multiple new studies from Italy, which primarily focused on patients with psoriasis receiving oral or biologic treatment, supporting our initial recommendation (guidance 1.1). [9][10][11] Additional new studies of patients with psoriatic arthritis (PsA) nested within cohorts of patients with rheumatic disease also suggest that they have similar rates of infection with SARS-CoV-2 and COVID-19 outcomes as the general population. [12][13][14] However, the risk of COVID-19 in autoimmune diseases was higher than in control patients (odds ratio [OR], 2.19; 95% confidence interval [CI], 1.05-4.58) in a meta-analysis of 7 case-control studies.…”
Section: Capsule Summary Dmentioning
confidence: 99%
“…Using randomized clinical trials (compared overall infection rates, rates of upper respiratory infections and nasopharyngitis), Lebwohl et al have found that the rates of nasopharyngitis and upper respiratory tract infections are similar to placebo [ 160 ]. Similarly, compared to the general population, there is no increased susceptibility for SARS-CoV-2 infection or increased severity of the disease course of COVID-19 in patients with psoriasis receiving systemic treatments, including biologics [ 161 ]. These studies suggested that biological therapy should be continued in patients with immune-mediated skin diseases during the COVID-19 outbreak.…”
Section: Sars-cov-2 and Autoimmune Diseasesmentioning
confidence: 99%
“… 6 Although the impact of these therapeutic options on increasing the risk of SARS-CoV-2 infection and disease severity remained somewhat uncertain for a long period, national and international guidelines on the topic were gradually updated based on the clinical experience. 7 11 More recently, guidelines on the appointment structure (in-person versus virtual), prioritization of clinical admissions (urgent versus less urgent), and the frequency of visits have also been developed. 7 – 12…”
Section: Introductionmentioning
confidence: 99%
“… 7 11 More recently, guidelines on the appointment structure (in-person versus virtual), prioritization of clinical admissions (urgent versus less urgent), and the frequency of visits have also been developed. 7 – 12…”
Section: Introductionmentioning
confidence: 99%